As Genis da internet: a efetividade do Sistema Interamericano de Direitos Humanos no enfrentamento da violência virtual contra a mulher - Walder, Laleska Rigatto (2021)
Human rights, although today understood as indivisible and universal, are the result of conflicts marked by pain and blood. In the course of the History, the comprehension of the supreme dignity was not an isonomic process. This is because especially black and indigenous women – same as those who are economically marginalized – for a long time were not seen as holders of human rights. As an integral part of the recognition process, the Inter-American System for the Protection of Human Rights (ISHR) was an essential tool for the recognition of the minorities as beings endowed with dignity. In this context, this dissertation intends to investigate the crime of revenge porn – understood as the unlawful disclosure or promotion of intimate material – in its historical, statistical and legal perspective, in the international human rights scenario. For this purpose, it is intended to study the women's historical trajectory as a claimer of their own sexuality, evidencing the weight of gender standards, rape culture and the patriarchal system as obstacles for their emancipation. Using art as a critical form to analyze the reality, the song “Geni e o Zepelim” (1993), by the composer Francisco Buarque de Hollanda, serves as a reference for the title of this work and as a metalinguistic north of the studied phenomenon. After the statistical survey of the penalization process in the Brazilian context, that entailed in the Law 13.718/2018, it is concluded that the unrestrained classification of legal assets generates the overload of justice and the impracticability of alternatives to punishment, resulting in everything, except in the damage reduction to the victim of nonconsensual exposure, or in preventing future cases. Finally, as a central objective of this work, the challenges of the ISHR to face the unlawful disclosure or promotion of intimate material will be exposed, demonstrating that, despite its unquestionable advances in the international field, there is still a long way to the effectly protection of women, mainly in the invisible and infinite environment of the internet